How Consumers Respond to Corporate Social Responsibility Initiative: Cause Related Marketing vs Philantrophy - Pertiwi, Lisia Astari; Balqiah, Tengku Ezni (UI Scholars Hub, 2021)
Increasing in demand of CSR from various stakeholders has caused company¡¯s CSR motives to be more complex. CSR activities are not only founded on the benevolence of corporate agents but also as part of a corporate strategy formulated in pursuit of stakeholder interest. This study investigate whether CSR motives could enhance customer trust and satisfaction. Focus on two CSR initiatives conducted by GrabTaxi (transportation industry) and Alfamart (retail industry), the purposes is to demonstrate how two type CSR initiative could delivered perceived motives and create loyalty. Cross-sectional offline and on- line survey was conducted on 175 respondents of GrabTaxi and 192 respondents of Alfamart. Structural Equation Interestingly, even though respondent perceived firm-serving motives (as strategic objectives) and reactive motives (as expected by stakeholder), CSR initiative could create trust and satisfaction.Struc- tural Equation Modelling as data analysis to test 5 hypotheses. The results show slightly different in the context of cause-related marketing (GrabTaxi), and philanthropy (Alfamart). Even though all respondents perceived that CSR is motivated by mix motives (benevolent and strategic), how these motives influence trust, satisfaction, and further loyalty are different. Two-type of CSR initiative ie Cause Related Market- ing (CrM) and philanthropy can provide firm-serving motive, public serving motive and reactive motive. These motives could encourage trust and satisfaction through path motive-trust-satisfaction (directly or indirectly through trust)-customer loyalty. Interestingly, even though respondent perceived firm-serving motives (as strategic objectives) and reactive motives (as expected by stakeholder), CSR initiative could create trust and satisfaction.